Antigenic and molecular evidence of Brucella sp.-associated epididymo-orchitis in frugivorous (Artibeus lituratus) and nectarivorous (Glossophaga soricina) bats in Brazil - Silva, Laice A.; Souza, Monique F. S.; Torquetti, Camila G.; Freitas, Daniele C. O.; Moreira, Larissa G. A.; Carvalho, Thaynara P.; Santana, Clarissa H.; Thompson, Julia R.; Rosa, Daniela C. O.; Jesus, Tatiana R.; Paixão, Tatiane A.; Santos, Renato L. (Frontiers in Veterinary Science, 2023)
This study included 47 free-ranging bats from the State of Minas Gerais, Brazil. Six bats (12.8%) had genital inflammatory lesions, and two of them (one Artibeus lituratus and one Glossophaga soricina, a frugivorous and a nectarivorous, respectively) were diagnosed with Brucella sp. infection by PCR and detection of antigens in intralesional macrophages by immunohistochemistry.